BUMdes Management And Finance Training In Marafenfen, South Aru District - Temalagi, Selva; Uniberua, Stivan H.; Pasamba, Ester M. (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The main objective of this study is to improve the management of Village-Owned Enterprises (BUMDes) in Marafenfen Village, Indonesia. Despite the village's beautiful natural potential, it is noted that tourism management has not been optimal. The lack of facilities, access, and management of BUMDes are obstacles in exploring the tourism potential. Method: To overcome these management problems, the team will provide training on understanding and managing management and finance. This training will focus on the management of BUMDes in border small islands, with materials covering organizational management, marketing, finance, sharia, and entrepreneurial skills. Training participants will involve village officials, BUMDes managers, and the community. Practical Applications: The practical application of this study is the implementation of the training program. The training is expected to improve the ability of BUMDes managers in identifying and developing business opportunities, especially in the tourism sector. This could potentially lead to an increase in the welfare of rural communities through improving the economy, creativity of low-income members, and the development of informal sector micro-enterprises. Conclusion: After the training, an evaluation will be conducted to get feedback from participants regarding the implementation of the training. The feedback will be used to make necessary improvements and adjustments for future training and development programs. The ultimate goal is to optimize the tourism potential of Marafenfen Village through effective BUMDes management.